Soya-cerebroside reduces interleukin production in human rheumatoid arthritis synovial fibroblasts by inhibiting the ERK, NF-κB and AP-1 signalling pathways. Issue 1 (1st January 2020) - Lee, Hsiang-Ping; Wu, Yang-Chang; Chen, Bo-Cheng; Liu, Shan-Chi; Li, Te-Mao; Huang, Wei-Chien; Hsu, Chin-Jung; Tang, Chih-Hsin
ABSTRACT: Rheumatoid arthritis (RA) is characterised by the infiltration of a number of proinflammatory cytokines into synovial fluid. Soya-cerebroside, an extract from Cordyceps militaris, inhibits synovial inflammation and reduces cartilage damage in an osteoarthritis model, although the role of soya-cerebroside in inflammatory cytokine expression in RA is uncertain. In this study, Gene Expression Omnibus (GEO) database records revealed higher levels of interleukin (IL)-1β, IL-6 and IL-8 in RA tissue compared with normal tissue. Elevated levels of these inflammatory cytokines were also higher in mice with collagen-induced arthritis (CIA) than in control mice. Soya-cerebroside effectively inhibited IL-1β, IL-6 and IL-8 expression in RA synovial fibroblasts, apparently by inhibiting the ERK, NF-κB and AP-1 signalling pathways. This anti-inflammatory agent shows promise for the treatment of RA.